A Unified Modeling Approach to Data-Intensive Healthcare - Buchan, Iain; Winn, John; Bishop, Christopher (The Fourth Paradigm: Data-Intensive Scientific Discovery, 2009)
The quantity of available healthcare data is rising rapidly, far exceeding the capacity to deliver personal or public health benefits from analyzing this data. Three key elements of the rise are electronic health records (EHRs), biotechnologies, and scientific outputs. We discuss these in turn, leading to our proposal for a unified modeling approach that can take full advantage of a data-intensive environment.